Plataforma hardware-in-loop para ensaios automatizados de inversores conectados à rede em múltiplos ambientes e condições de operação - Menegazzo, Luiz Fernando Rissotto (2023)
With the increasing demand for renewable energy sources, the use of inverters in power systems has rapidly grown. To ensure the safety and efficiency of inverters, it is necessary to test them under a variety of operational conditions, including variations in voltage and frequency of the power grid, as well as different grid impedances. However, testing on test benches can be expensive and require specialized personnel. To facilitate the development and testing of inverters, this dissertation proposes the development of an automated testing platform based on Python and object-oriented programming, which allows tests to be performed in virtual environments: using Virtual-hardware-in-the-loop (VHIL); hybrid (real and virtual): using the Controller-hardware-in-the-loop (CHIL) technique; or fully real: using laboratory equipment automation. This platform can perform precise and efficient tests under a wide range of operational conditions and in accordance with current inverter certification standards such as ABNT NBR 16149, ABNT NBR 16150, IEC 61000-3-3, and INMETRO ordinance nº 140/2022, helping to reduce the time and costs associated with inverter development and testing. The platform’s unique feature is the ability to be adjustable to the user’s needs, allowing for testing of equipment still in the design or development phase, without necessarily having the power circuitry ready, as well as the ability to perform numerous iterations by automatically and rapidly changing test conditions, which would not be feasible manually.